2006
DOI: 10.1038/nn1736
|View full text |Cite
|
Sign up to set email alerts
|

UNC5A promotes neuronal apoptosis during spinal cord development independent of netrin-1

Abstract: In addition to their role as chemorepellent netrin-1 receptors, UNC5 proteins may mediate cell death because they induce apoptosis in cultured cells. To test this in vivo, we generated Unc5a (formerly Unc5h1) knockout mice and found that this deletion decreased apoptosis and increased the number of neurons in the spinal cord. In contrast, loss of netrin-1 (Ntn1) did not affect the amount of apoptosis, suggesting that NTN1 is not required for neuronal apoptosis in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 14 publications
4
46
0
Order By: Relevance
“…In this study it was found that death of embryonic motor neurons in UNC5A (a netrin receptor) Ϫ/Ϫ mice is reduced in vivo (Williams et al, 2006). Although the ligand responsible for the activation of UNC5A is not known, this result is consistent with the possibility that a balance between survival and death signals also determines the number of motor neurons.…”
Section: Semaphorin/plexina3 Signaling Effects On Drg Neuronal Cell Dsupporting
confidence: 73%
See 1 more Smart Citation
“…In this study it was found that death of embryonic motor neurons in UNC5A (a netrin receptor) Ϫ/Ϫ mice is reduced in vivo (Williams et al, 2006). Although the ligand responsible for the activation of UNC5A is not known, this result is consistent with the possibility that a balance between survival and death signals also determines the number of motor neurons.…”
Section: Semaphorin/plexina3 Signaling Effects On Drg Neuronal Cell Dsupporting
confidence: 73%
“…Ϫ/Ϫ (Williams et al, 2006) mutants, and may reflect the induction of compensatory nonapoptotic cell death mechanisms. The role of Sema3A as a death inducer in vivo is more complicated to evaluate.…”
Section: Semaphorin/plexina3 Signaling Effects On Drg Neuronal Cell Dmentioning
confidence: 99%
“…Axonal expression of UNC5A by spinal motor neurons on myelin was confirmed immunocytochemically using rabbit polyclonal antibodies against the intracellular domain of UNC5A (Ab 2026, kindly provided by Dr. Hinck, University of California, Santa Cruz, CA). Specificity of antibody 2026 for UNC5A has been well documented previously (Williams et al, 2003(Williams et al, , 2006.…”
Section: Methodsmentioning
confidence: 61%
“…Mice lacking DCC phenocopy the netrin 1 null mice remarkably closely (Fazeli et al, 1997), highlighting the role of DCC as a key netrin 1 receptor. Unc5a null mice are viable and live to adulthood, but exhibit reduced neuronal apoptosis (Williams et al, 2006). Unc5b knockout mice die during embryogenesis due to heart failure and substantial disruption of their vasculature (Lu et al, 2004).…”
mentioning
confidence: 99%